Pengembangan Media Nilai Nilai Egalitarianisme (Kesetaraan) Untuk Mereduksi Perundungan - Agustine Sandosa; Imaratul Ulwiyah; Mudafiatun Isriyah (Social Science Academic, 2026)
Bullying is one of the problems that still often occurs in the educational environment and can have a negative impact on the psychological, social, and academic development of students. One of the efforts that can be made to reduce bullying behavior is through the cultivation of egalitarianism or equality values that emphasize respect for individual rights, dignity, and differences. This research aims to develop learning media based on egalitarianism values as an educational means in reducing bullying behavior in students. The research method used is Research and Development (R&D) with reference to the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The products produced are in the form of learning media that contain material on equality, tolerance, empathy, and appreciation for diversity. The results of validation by media experts and material experts show that the developed media is in the category of very feasible to use. In addition, the results of the trial show that the use of these media is able to increase students' understanding of equality values and contribute to reducing the tendency of bullying behavior. Thus, the media of egalitarianism values developed can be an innovative alternative in supporting the creation of a safe, comfortable, and inclusive school environment.